2023
DOI: 10.1038/s41467-023-35922-5
|View full text |Cite
|
Sign up to set email alerts
|

Active mRNA degradation by EXD2 nuclease elicits recovery of transcription after genotoxic stress

Abstract: The transcriptional response to genotoxic stress involves gene expression arrest, followed by recovery of mRNA synthesis (RRS) after DNA repair. We find that the lack of the EXD2 nuclease impairs RRS and decreases cell survival after UV irradiation, without affecting DNA repair. Overexpression of wild-type, but not nuclease-dead EXD2, restores RRS and cell survival. We observe that UV irradiation triggers the relocation of EXD2 from mitochondria to the nucleus. There, EXD2 is recruited to chromatin where it tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Particularly, a previous study has indicated that S12 participates in the process of identifying codon and anticodon pairs, and in the subsequent conformational rearrangements of the 30S subunit ( Agarwal et al, 2011 ). RNA polymerase plays a critical role in gene expression, as it allows the genetic information encoded within DNA to be converted into functional RNA molecules ( Sandoz et al, 2023 ). The transcription of RNA polymerase rpoC (1_orf04248), rpoA (1_orf04149), rpoB (1_orf04250) increased as these were overexpressed in aG6 strain ( Figure 6 ; Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, a previous study has indicated that S12 participates in the process of identifying codon and anticodon pairs, and in the subsequent conformational rearrangements of the 30S subunit ( Agarwal et al, 2011 ). RNA polymerase plays a critical role in gene expression, as it allows the genetic information encoded within DNA to be converted into functional RNA molecules ( Sandoz et al, 2023 ). The transcription of RNA polymerase rpoC (1_orf04248), rpoA (1_orf04149), rpoB (1_orf04250) increased as these were overexpressed in aG6 strain ( Figure 6 ; Supplementary Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, UV damage can trigger global transcription suppression in trans besides directly blocking PolII elongation in cis, both of which are related to cell survival and RNA synthesis (57). As examples, both PAF1C and EXD2 played important roles in cell survival and recovery of RNA synthesis upon UV treatment by stimulating transcription restarting after damage, albeit they were not involved in TCR (58,59). Although the possibility that STK19 is also involved in transcription restarting independent of its role in TCR cannot be excluded, we demonstrated that STK19 is essential for TCR by directly measuring TCR with XR-seq and Damage-seq in HeLa and XP-C cells, respectively.…”
Section: Discussionmentioning
confidence: 99%